Relationship between latex yield of Hevea brasiliensis and antecedent environmental parameters - Raj S; Das G; Dey S K; Pothen J (International Journal of Biometeorology, 2005)
A study on the relationship between latex yield and antecedent environmental data was undertaken for five clones (RRII 203, RRII 118, RRIM 600, RRII 105 and GT 1) of Hevea brasiliensis (rubber) in Agarthala, northeast India, a region in which rubber is not traditionally cultivated. The explained variance for the regression equations based on parameters determined on the day of tapping and up to 3 days prior to it, varied from 72;to 37;during the NWT period and 94-83;during the WT period. SOil moisture storage, 1 and 3 days prior to tapping, was found to be the primary parameter affecting yield for the NWT and WT periods, respectively. It was observed that the clone RRII 105, with a comparatively lower yield to that of RRIM 600, was more susceptible to daily WD conditions during the non-winter season. RRIM 600 and RRII 105 being high-yielding clones were also found to be fairly dependent on the AT of the day prior to tapping. The mean lag period correlation of this parameter with yield was also found to be higher during the WT period than during the NWT period. As a whole, the mean lag period based on prior measurements of environmental variables showed optimum correlation with yield at 15-20 days prior to the day of tapping. The study also confirms that varied responses of yield with environmental factors in this non-traditional region of rubber cultivation depend on clonal character.
Keywords: Agoclimate; Lag period; Soil storage; Winter tapping period; Yield